Capacity constrained supply chains: a simulation study. (18th December 2008) - Cannella, Salvatore; Ciancimino, Elena; Marquez, Adolfo Crespo
This paper explores the relationship between constrained capacity and supply chain performance. Six capacity constraint levels are studied under different inventory policies and information sharing strategies. The results suggest that an increment of production capacity, used in industry as local approach to manage increasing incoming orders, does not necessarily imply an improvement in customer service. In presence of information distortions, the strategy of augmenting production capacity can lead to satisfy at a higher cost an over-estimated market demand. The collaborative practices provide bullwhip effect dampening and inventory stability, and increase the ability of the structure to avoid this risk.